Non‑synonymous polymorphisms in the HRC and ADRB1 genes may be associated with all‑cause death in patients with non‑ischemic heart failure - Tanise Telles; Bruna Miers May; Maurício Pimentel; Bruna Pereira; Michael Éverton Andrades; Luís Eduardo Paim Rohde; Kátia dos Santos (2023)
Sudden cardiac death (SCD) is an unpredictable and common mode of death in patients with heart failure (HF). Alterations in calcium handling may lead to malignant arrhythmias, resulting in SCD, and variants in calcium signaling-related genes have a significant association with SCD. Therefore, the aim of the present retrospective cohort study was to investigate the association of Ser96Ala [histidine-rich calcium-binding protein (HRC)], Ser49Gly [β1-adrenergic receptor (ADRB1)], Arg389Gly (ADRB1) and Gly1886Ser [ryanodine receptor 2 (RYR2)] polymorphisms with serious arrhythmic events and overall mortality in patients with HF with reduced left ventricular ejection fraction of non-ischemic etiology. In total, 136 patients with HF underwent physical examination, routine laboratory tests, non-invasive assessment of cardiac function and an invasive electrophysiological study. The primary outcome was the occurrence of serious arrhythmic events, set as either SCD or appropriate implantable cardioverter-defibrillator (ICD) therapy, and the secondary outcome was all-cause death. During a median follow-up of 37 months, arrhythmic events occurred in 26 patients (19%) and 41 patients (30%) died. Patients carrying the Ser allele of the Ser96Ala polymorphism in HRC had worse survival than those with the Ala/Ala genotype (log-rank P=0.043). Despite the difference in survival time, the Ala/Ala genotype was not associated with all-cause death in the regression analysis [unadjusted hazard ratio (HR)=0.17; 95% CI, 0.02-1.21]. Regarding the Ser49Gly and Arg389Gly polymorphisms in ADRB1, homozygosity for the major alleles at both sites (Ser49Ser and Arg389Arg) was associated with a two-fold increased risk of all-cause death compared with the other genotype combinations (unadjusted HR=1.98; 95% CI, 1.02-3.82). However, this association was lost after controlling for clinical covariates. No association was observed for the Gly1886Ser polymorphism in RYR2. Overall, the present findings are concurrent with the hypothesis that the Ser96Ala (HRC), Ser49Gly (ADRB1) and Arg389Gly (ADRB1) polymorphisms may be associated with HF prognosis. In particular, the Ser96Ala polymorphism might aid in risk stratification and patient selection for ICD implantation.